Plants for the Ancestors: Traditional Knowledge and Beliefs of the Mentawaians on Siberut Island. - Delfi, Maskota; Laurens Bakker; Nguyen Thanh Tuan; Johan Weintre (Universitas Andalas, 2025)
Plants for the ancestors that entail the traditional knowledge and beliefs of the Mentawaians on Siberut Island, is exclusive traditional knowledge of the indigenous people of Mentawai. Traditional Ecological Knowledge (TEK) is one of the most fascinating knowledge sources and valuable to preserve and explore for future regional importance as many types of ethno botanical products remain unexplored. When viewing western medicine supplied at the pharmacy, it has to be realised that many started their medicinal use in a village somewhere close to a forest of field. A clear example would be the use of opium and the many healing derived components in modern medicinal treatment. Industrial produced based pharmaceutical medicine has often been synthesised from the ethno-pharmacological range of herbal medicines and new components discovered in nature. By consulting the knowledge of traditional healers, possible new cures might be encountered from our natural environment. In Indonesia the importance of TEK has been particularly stimulated by the introduction of regional autonomy in the year 2000. It has reinforced indigenous political as well as regional economic power, to develop local natural resources for a national and international trade. It has introduced an economic development that has strengthened awareness of local botanical potential and involvement of gender opportunities in a resurge of interest in medicinal plants and domestication in Mentawaian herbal gardens.